Self- Awareness of Emotions and its Relation to the Way of Helping of Kindergardens' Children - تقوى محمد خضير أ.م.د.زينب محمد كاطع (College of Education for Women, 2019)
The self-awareness interactions reflects with emotions,assess the child in respect to its relations with the social standards; they are not merely simply reactions , but rather they connect with his moral behavior and other 's thinks. When the self- awareness gets developed with emotions within the child , the latter become highly sensitive, causing him prone to be blamed . AS a result , the children test the self -awareness interactions with emotions and in age 3 years , where the self -awareness interactions with emotion clearly link to the self- assessment. The children in stage of kindergarten could not describe the self-awareness interactions accurately ; they test it under different circumstances in comparison to the youngest one. Based on the recommendations of emotionally child bringing up conference held in Cairo in 2007, it is necessitated to concern over the official and semi- official educational institutions that could have an emotion effect upon the child ; besides, the conference also confirmed to study the child emotionally and how to promote it for bringing up a new generation endowing with strong will and sincere ( Al-Hawarna- 2007). The study has indicated that the self-awareness with emotions and its integration with others have a relation to appear behavior problems within the children and having a big role on the psychological and social development for the children. The self-awareness with emotions has an important impact on the children for a success in life and for preserving the relations with the family and colleagues. If the children are not to be aware with their emotions , they will find difficulty in making decisions logically or to get integrated with others ; thus , they have an opportunity to response to the social attitudes to help others in correct ways and to avoid the decisions that lead to incorrect results( Elias and Weissber 2000). The two researchers have indicated that the child needs to learn some vocabularies indicating to emotions and feelings and reasons for such reasons and other alternatives in order for the child to have an opportunity to represent his emotions to be used in correct way. . ( Al-Shimari-2005) sees that the method of assistance represents as a means for social interaction having clear effect in the exchange between the individual and his family and between the individual and others ( Al-Shimari , 2005, 98). The current research aims to : Measure the self- awareness with emotions with the kindergarten children ( sample of the research males and females ) Measure the method of assistance within the kindergarten children ( sample of the research males and females ) Knowing the relationship between the self- awareness with emotion and integration with others among the kindergarten children. ( males and Females) For verifying goals of the research , the researcher has prepared three scales ( scale of self-awareness with emotion, scale of integration with others and scale of assistance ) . For ascertaining the reliability and consistence, the three scales have been applied on the sample 400 child who have been randomly chosen from 20 kindergartens . After processing the statistic data , the scales have been applied on the basic sample 600 child who have been randomly chosen . The researcher has reached to the following results: The sample of the research of females enjoys with self-awareness with emotion. The sample of the research of females enjoys with integration with others The research sample of females enjoys with the method of assistance.The integration with others is consistent relationship , the more the integration with others gets increased , the more the self-awareness with emotion increase. The more the method of assistance increases , the more self-awareness with emotion increases. The independent variables affect the method of assistance. In the light of the results , the researcher has submitted a set of recommendations and suggestions.